The Three Seas Initiative: Involvement and priorities of Estonia, Latvia and Lithuania - Lesiewicz, Elżbieta; Włodarska-Frykowska, Agata; Jundo-Kaliszewska, Barbara (Studia Polityczne, 2025)
Due to their size and limited economic opportunities, the Baltic states are looking for development opportunities within various political formats. One of them is the 3SI Initiative. The aim of the article is to present the current priorities and the degree of involvement of Lithuania, Latvia and Estonia in the projects of the 3SI initiative. Since 2015, the countries have been working together to achieve better integration of the region, strengthen security areas, competitiveness of energy supplies and integration of transport pillars. What seems to be crucial is cooperation in the digital sphere, which currently has a direct impact on the security of the 3SI member states. The war in Ukraine, Russia’s policy towards minorities living in all Baltic states, as well as Japan’s accession as a strategic partner to 3SI, motivate Latvia, Lithuania and Estonia to take dynamic steps towards further integration.